Taking the Pulse of Planet Earth: A Proposal for a New Multi-disciplinary Flagship Project in Canadian Solid Earth Sciences - Bleeker, Wouter (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2004)
SUMMARY Herein I propose a vision for a new multidisciplinary "big science" project for Canada's solid earth sciences. I call this proposed project: "Taking the Pulse of Planet Earth". At a modest cost, and over a 5 to 10 year life-span, it would aim at providing the most comprehensive and multidisciplinary knowledge base of the complete record of mafic magmatism in and around Canada, and through stimulating international cooperation, around the world. A complete record of mafic magmatism (spatial distribution, ages, periodicities, rates, volume estimates, estimated geochemical fluxes to atmosphere and hydrosphere, tectonic settings, structural trends, sequence stratigraphic framework, evolving major and trace element compositions, evolving isotopic ratios, paleomagnetic information, paleo-intensities, associated ore deposits, etc.) constitutes critical input data for numerous first-order questions about the past and present evolution of our planet. Many of such questions relate to issues that are currently a focus of attention: global change, past climate extremes, complex Earth systems, planetary evolution, extinction events, flood volcanism, potential relationships with large impact events, and the discovery of new ore resources. The proposed project is a focused, "smart", and highly efficient approach to solve a large number of these seemingly unrelated but first-order questions in contemporary earth science. At its core, it would have a large dating program, aiming to provide approximately 200 new, high-precision ages of mafic magmatic events across Canada and adjacent regions. A Supporting Geoscience grant system would ensure that other aspects of the magmatic record receive equal attention. Finally, I illustrate the impact this project would have on paleocontinental reconstructions. As part of this illustration, I synthesize existing data on two dyke swarms, the ca. 2.45 Ga Matachewan and Kaminak swarms, respectively, and propose a novel Superior-Hearne reconstruction within supercraton Superia.